Dimensi Charity Perbankan Syariah - Saiful Bahri (JPS (Jurnal Perbankan Syariah), 2020)
There are too many words of Allah in the Qur'an regarding donations and alms, at the same time it states that this charity instrument is a fundamental and principal variable in Islamic law which is actually a way of life. The urgency of charity is not only for individuals, but also very useful for financial institutions such as Islamic banking. With the intensification and extensification of charity, it is imperative that these financial institutions gain good blessings in the world, especially for bankers in the afterlife. With a simple method, namely descriptive analysis, this study describes as few facts as the authors know and understand in order to become a source of inspiration for the next good.